Another CMI problem: (and I could solve this)

Define polynomials \( P_n(x) \) in this way:

\( \displaystyle P_0(x) = 1 \)

\( \displaystyle P_n(x) = \dfrac{x(x-1)(x-2)\ldots(x-n)} {n!} \) where \( n \) is a positive integer.

Prove that for any polynomial \( f(x) \), there always exist *unique* real numbers \( b_0, b_1, \ldots b_n \) such that:

\( \displaystyle f(x) = \sum_{0 \le i \le n} b_i p_i (x) \)

Further prove that the \( b_i \)'s are all integers, if it is given that \( f(m) \) is an integer for each integer \( m \).

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestNote that the polynomials \(P_i(x), 0\leq i \leq n\) have increasing degrees and hence they are

linearly independentin the vector space of polynomials of degree \(n\). Hence they form abasisand the proof for the first part follows.Log in to reply

Part (a): Proving the existence and uniqueness of \({b_i}\):

Let \( f(x)= c_0 +c_1x +c_2x^2+...+c_nx^n\) and take note of the fact that:

\(p_n(x)= \dbinom{x}{n}(x-n)\). Since \(p_0(x)=1\), we may write:

\(\sum_{0 \le i \le n}(b_i)(p_i(x)) = (b_0)+ \sum_{1 \le i \le n}(b_i)(p_i(x))\)

Expanding \(\sum_{1 \le i \le n}(b_i)(p_i(x))\): (Without loss of generality, assume \(\sum_{1 \le i \le n}(b_i)(p_i(x))\)= \(\sum_{i=1}^{n}(b_i)(p_i(x))\))

\(\sum_{i=1}^{n}(b_i)(p_i(x))\))= \(b_1(x^2-x)+\frac{b_2}{2}(x^3-3x^2+2x)+\frac{b_3}{6}(x^4-6x^3+11x^2-6x)+\frac{b_4}{24}(x^5-10x^4+35x^3-50x^2+24x)+... +\frac{b_nx!(x-n)}{n!(x-n)!}\)

Equating coefficients of f(x), \(c_i\), with those of \(\sum_{i=1}^{n}(b_i)(p_i(x))\)):

\(c_0=b_0\)

\(c_1=-b_1+b_2-b_3+b_4+....=\sum_{i=1}^{n}(-1)^ib_i\)

\(c_2=b_1-\frac{3}{2}b_2+\frac{11}{6}b_3-\frac{50}{24}b_4+....\)

\(c_3= \frac{b_2}{2} - b_3 +\frac{35}{24}b_4-....\)

\(c_4= \frac{b_3}{6} - \frac{10}{24}b_4+.....\)

\(c_5= \frac{b_4}{24}+....\)

This is a linear system of n equations (excluding \(c_0=b_0\)) in n unknowns. Therefore, we may construct an n x n matrix A such that: \(A\vec{b}=\vec{c}\), where \(\vec{b}\) contains all \(b_i\) and \(\vec{c}\) contains all \(c_i\). \(A=\)

\[ \begin{pmatrix} -1 & 1 & -1&...&\alpha_1 \\ 1 & \frac{-3}{2} & \frac{11}{6}&...&\alpha_2 \\ 0 & \frac{1}{2} & -1&...&\alpha_3\\ 0&0&\frac{1}{6}&...&\alpha_4\\ .&.&.&.&.\\ .&.&.&.&.\\ .&.&.&.&.\\ 0&0&0&....&\alpha_n\\ \end{pmatrix} \]

\(A\vec{b}=\vec{c}\) has a unique solution if and only if A is an invertible matrix. A is invertible if and only if \(det(A)\neq 0\). Then \(A\vec{b}=\vec{c}\) has a unique solution if and only if \(det(A)\neq 0\). If we use Gaussian Elimination to reduce A, that is, if we add line (1) to line (2), then line (2) to line (3), then line (3) to line (4), etc. we see that A will be reduced to an upper triangular matrix with every term on the main diagonal of A of the form: \(A_{ji}=\frac{-1}{i!}\), where i corresponds to the column number of \(A_{ji}\). Hence \(det(A)=\prod_{i=1}^n\frac{-1}{i!}\).

Since \(det(A)=\prod_{i=1}^n\frac{-1}{i!}\) and \(i\ge1\), \(det(A)\neq 0\). Then A is invertible and \(A\vec{b}=\vec{c}\) has a unique solution, hence \(\vec{b}=A^{-1}\vec{c}\), which of course exists. This proves the existence of \(b_i\) but does not prove the uniqueness of all \(b_i\). We will now proceed to prove this.

Let \(A_{ji}^{-1}\) denote the element of \(A^{-1}\) in the \(j^{th}\) row and \(i^{th}\) column. Since \(\vec{b}=A^{-1}\vec{c}\), we have:

\(b_n=A_{n1}^{-1}c_1 + A_{n2}^{-1}c_2+A_{n3}^{-1}c_3+...+A_{nn}^{-1}c_n\)

Suppose \(\exists\) \(b_i\) such that \(b_i=b_n\) but \(i \neq n\), i.e. suppose all \(b_i\) are not unique. Then, since \(b_n\) is described by the above equation:

\( A_{i1}^{-1}c_1=A_{n1}^{-1}c_1\)

\( A_{i2}^{-1}c_2=A_{n2}^{-1}c_2\)

\( A_{i3}^{-1}c_3=A_{n3}^{-1}c_3\)

And in general: \( A_{in}^{-1}c_n=A_{nn}^{-1}c_n\) \(\Rightarrow\) \( A_{in}^{-1}=A_{nn}^{-1}\)

If \( A_{in}^{-1}=A_{nn}^{-1}\) and \(i \neq n\), then \(A^{-1}\) contains at least two identical rows, which implies \(det(A^{-1})=0\). Then \(A^{-1}\) is not invertible, which is impossible because \((A^{-1})^{-1}=A\). This is a contradiction, hence we are forced to conclude that all \(b_i\) are unique. Part (b) coming soon.

QED

Log in to reply

did any one get a seat in CMI (i got one wihtout interview) i solved nearly 6 of the ques....

Log in to reply

I did (without interview). Didn't expect it though! Pretty much set on joining there.

Log in to reply

Other problems I found interesting:

And you thought limits were always easy

A fun problem - Find the formula of number of functions from a power set to another set

Log in to reply

Solved this one. Nice question.

Log in to reply

How do you solve this question? Can you give the solution? Or atleast an hint

Log in to reply

Hint: Notice that \( P_k (x) \) vanishes at \( x = k \), and also do the "higher" \( P \)'s. That is, \( P_{k+1}, P_{k+2} \) and so on. But the "lower" \( P \)'s don't. If you use this properly, you're done!

Log in to reply

Log in to reply